Lymphoplasmacytic meningioma: A rare case report - DasNayak, Goutami; Mishra, Pratiksha; Patra , Yugosmita; Pradhan, Dilleswari (Journal of Pathology of Nepal, 2024)
We report a case of 51-year-old female with lymphoplasmacyte-rich meningioma, which is a rare histological subtype of meningioma. It often mimics intracranial inflammatory lesions during its initial course. Hence, early and accurate recognition is essential for proper management. Histopathology is the gold standard, and immunohistochemistry aids in final diagnosis of this tumor.